Microcontroller Based Flexible Modulation Scheme of MLI Operation for Selective Lower Levels: A Knowledge Based Approach - R. K. Dhatrak; R. K. Nema; D. M. Deshpande (Journal of Engineering)
In today’s industrial world multilevel inverter (MLI) got a significant importance in medium voltage application and also a very potential topic for researchers. It is experienced that studying and comparing results of multilevel inverter (MLI) at distinct levels are a costlier and time consuming issue for any researcher if he fabricate different inverters for each level, as designing power modules simultaneously for different level is a cumbersome task. In this paper a flexible quotient has been proposed to recognize possible conversion of available MLI to few lower level inverters by appropriately changing microcontroller programming. This is an attempt to obtain such change in levels through simulation using MATLAB Simulink on inductive load which may also be applied to induction motor. Experimental results of pulse generation using dsPIC33EP256MC202 demonstrate the feasibility of proposed scheme. Proposed flexible quotient successfully demonstrates that a five-level inverter may be operated as three and two levels also. The paper focuses on odd levels only as common mode voltage (CMV) can be reduced to zero and performance of drives is better than even level. Simulated and experimental results are given in paper.